Manoharachariomyces, a new hyphomycetous fungus from India - and I.K. KUNWAR, N. KRISHNA RAO, D.K. AGARWAL (Indian Phytopathology, 2005)
A new anamorphic fungus Manoharachariomyces characterized by macronematous, loosely synnematous, fasiculate conidiophores and lageniform conidiogenous cells producing solitary, transversely septate, broadly ovoid, aerogenous conidia is proposed with Manoharachariomyces lignicola as the type species.